ANALISIS PERSISTENSI LABA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2020-2021 - Stefhani, Yosi; Febrianti, Hana Difa (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2023)
The purpose of this study is to analyze the impact of Accrual Reliability, Operating Cash Flow, Sales Volatility, and Company Size on the Profit Persistence of the company. The sample consists of 29 manufacturing companies listed on the Indonesia Stock Exchange during the 2020 – 2021 period, selected using a purposive sampling method. Data analysis involved a descriptive approach and multiple linear regression. The data used is secondary. The results of the partial test show that Accrual Reliability, Operating Cash Flow and Sales Volatility affect Earnings Persistence, while Company Size has no significant effect. Overall, the test results state that Accrual Reliability, Operating Cash Flow, Sales Volatility, and Company Size simultaneously affect Earnings Persistence.